Soil microbiota plays a key regulatory role in the outbreak of tobacco root rot - Li, Pengfei; Gu, Songsong; Zhu, Yanmei; Xu, Tianyang; Yang, Yishuai; Wang, Zhengqiang; Deng, Xiangdong; Wang, Bin; Li, Wei; Mei, Wenqiang; Hu, Qiulong (Frontiers in Microbiology, 2023)
The fungal pathogen Fusarium sp. causes root rot, a major problem for tobacco cultivation in China, resulting in significant economic losses. However, there is only a limited understanding of the interactions between this pathogen and other members of the soil microbial community. In this study, we used high-throughput sequencing technology to evaluate the soil prokaryotic, fungal and protistan communities, and found that infected soil had higher levels of soil nutrients but lower observed richness within all three microbial groups compared to healthy soil from the same field. The abundance of the pathogenic fungi Fusarium solani f sp eumartii was significantly higher in infected soil. pH was found to significantly influence the composition and structure of the microbial communities. Infection by F. solani had a significant impact on the microbial community structure and interactions in soil, leading to a reduction in network scale and the number of keystone species. Additionally, the role of prokaryotes in the invasion of F. solani was evaluated, with the results showing that F. solani had a higher number of connecting nodes in infected soils. Interestingly, the relationships between predatory protists and fungi were increased, while the predation of F. solani decreased. Overall, this study highlights the importance of understanding the interactions among microorganisms in the soil ecosystem and the vulnerability of soil microbial communities to pathogen invasion.